Preliminary exploration of theory and practice training of 5G ultrasonic remote consultation in grassroot hospitals - Ceng Wang; Yi Zheng; Cui Xiong; Litao Sun; Jing Wang (BMC, 2022)
Abstract Background With the rapid development of science and technology, telemedicine diagnosis and treatment systems have gradually attracted increased attention and applications.5G ultrasound is an important branch of telemedicine, connecting grassroots hospitals at one end and provincal hospitals at the other, which provides remote guidance to grassroots doctors for ultrasound examination and image diagnosis. It is convenient for villagers obtaining diagnosis and advice from provincial ultrasound experts, saving time and economic costs, as well as benefiting from high-quality ultrasound medical resources. In this study, taishun County community grassroot hospitals were selected as the pilot study of 5G ultrasound application, to explore the effectiveness of their theory and practice, and gradually improve the remote ultrasound diagnosis and treatment standards, so as to improve their quality of grassroots hospitals and benefit grassroots people.  Methods This is a descriptive study. The Provincal Hospital will conduct ultrasonic theory and practice training for grassroot hospitals. The training subjects included 43 doctors in grassroots hospitals who were willing to carry out ultrasound examinations. Theories, skills training scores and trainees' questionnaires on teaching content were collected and analyzed. After passing theoretical and practical training, they will conduct ultrasound examinations in their respective communities and collect relevant cases. There are 148 cases thus far for analysis. It mainly included the type of disease, whether the patient was out-patient or inpatient, frequency of ultrasound visits in recent 5 years, and follow-up treatment measures. Results It mainly included three aspects: (1) Through theoretical and practical training, the ultrasonic diagnosis level of grassroot doctors was significantly improved. The difference in scores between the two practical trainings was statistically significant. (2) Forty-three questionnaires were sent out, feedback from trainees was very high. Most of them was very satisfied with our training. The total score of the questionnaire was 10, and 97.67% of them score more than 8. (3) In total, there were 148 remote consultation cases, including 67 males and 81 females, who were aged 21 to 101 years old (62.40 ± 15.73).mainly abdominal ultrasound, and typical cases involve fatty liver, hepatic cyst, gallbladder stone, kidney stone and so on. We analyzed case data and provided follow-up treatment recommendations. Conclusion As a "visual apparatus", 5G ultrasound can be routinely carried out in grassroot hospitals, which can provide mutual benefit between doctors and patients and comprehensively promote healthy villages.